Development and validation of an ELISA for a biomarker of thyroid dysfunction, thyroid peroxidase autoantibodies (TPO-Ab), in dried blood spots - Geeta N. Eick (2020)
© 2020 The Author(s). Background: The prevalence of allergic and autoimmune conditions has been steadily increasing in wealthy nations over the past century. One hypothesis put forward to explain this is the Old Friends Hypothesis, which posits that increased hygiene, urbanization, and lifestyle changes have reduced our exposure to parasites and microbes that we co-evolved with, resulting in immune dysregulation. However, research in traditionally living populations, who are exposed to greater parasite and pathogen loads such as those encountered during our evolution, is limited, in part due to a lack of minimally invasive, field-friendly biomarkers of autoimmune disorders. We therefore developed an ELISA to assess positivity for thyroid peroxidase autoantibody (TPO-Ab), an indicator of autoimmune thyroid disease, based on dried blood spot (DBS) samples. Results: We used the Accubind anti-thyroid peroxidase test system to screen our validation samples comprising matched fingerprick DBS, venous DBS, and plasma samples from 182 adults. After confirming that we had TPO-Ab-positive individuals in our validation sample (n = 12), we developed an indirect ELISA to measure TPO-Ab levels from one 3-mm DBS punch. The sensitivity and specificity of our assay for DBS samples ranged from 91.7-100% and 98.2-98.8%, respectively, using a cut-off value of ≥ 26 IU/mL. Intra-assay reliability for duplicate quality control DBS punches was 5.2%, while inter-assay reliability ranged from 11.5-24.4% for high, medium, and low DBS controls. Dilutional linearity ranged from 80 to 120%, and spike and recovery experiments indicated that the DBS matrix does not interfere with the detection of TPO-Ab. TPO-Ab levels remained stable in DBS samples stored at - 28 °C or - 80 °C, but decreased over time in DBS samples kept at 22 °C or at 37 °C. Conclusions: We developed an in-house, kit-independent indirect ELISA assay to determine individuals' TPO-Ab positivity based on dried blood spots, representing a cost-effective method with potential applications in a range of research settings.